(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The study investigated the levels of psychological burning among female teachers of students with special mental needs, according to variables: (government or private institutes), (academic qualification), (years of experience). The sample consisted of (60) female teachers in the special mental needs of development institutes in Swaida.A psychometric scale was used by the researcher, a developer of the Maslach list for psychological Burning, distributed among three dimensions (emotional exhaustion –numbness of feeling- low sense of achievement), where its validity and reliability has been calculated, the statistical analysis showed: - There was an average level of psychological burning among special mental needs female teachers. -There were statistically significant differences in the degrees of psychological burning according to the academic qualification, female teachers who have (intermediate institute) have more psychological burning than who have (university degrees). - There were statistically significant differences in psychological burning degrees according to (years of experience), female teachers with experience less than five years have more psychological burning than who have more five years. - There were no statistically significant differences in the degrees of psychological burning according to the variable of (government or private institutes).